1979
DOI: 10.1128/jb.138.2.370-376.1979
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a succinate dehydrogenase complex solubilized from the cytoplasmic membrane of Bacillus subtilis with the nonionic detergent Triton X-100

Abstract: A succinic dehydrogenase (SDH) complex has been purified from Triton X-100-solubilized membranes from Bacillus subtilis by precipitation with specific antibody. Radioactively labeled precipitated complex was analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis followed by autoradiography of the gels. The complex contained equimolar amounts of three polypeptides with approximate molecular weights of 65,000, 28,000, and 19,000. Five succinic dehydrogenase-negative mutants, belonging to the citF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 19 publications
3
32
0
Order By: Relevance
“…The cytochrome is the detergent binding, hydrophobic part of the reductase (H. Weiss, personal communication). A similar monodisperse SDH-cytochrome b complex containing SDH and a detergent binding (unpublished experiments) cytochrome bw polypeptide in an equimolar amount to SDH has also been isolated from Triton X-100-solubilized B. subtilis membranes (39,40) (Table 3). It is not known if this complex has quinone reductase activity.…”
Section: Membrane Bindingmentioning
confidence: 97%
See 1 more Smart Citation
“…The cytochrome is the detergent binding, hydrophobic part of the reductase (H. Weiss, personal communication). A similar monodisperse SDH-cytochrome b complex containing SDH and a detergent binding (unpublished experiments) cytochrome bw polypeptide in an equimolar amount to SDH has also been isolated from Triton X-100-solubilized B. subtilis membranes (39,40) (Table 3). It is not known if this complex has quinone reductase activity.…”
Section: Membrane Bindingmentioning
confidence: 97%
“…These results strongly suggest the presence of a limiting number of specific SDH-binding sites in the B. subtilis cytoplasmic membrane. Evidence that cytochrome b5w is (part of) this binding site is provided by the observations that (i) cytochrome b5,m is present in stoichiometric amounts in the Triton X-100-solubilized, purified membrane SDH complex (39,40) and (ii) mutants which specifically lack cytochrome b&% contain the SDH Fp and Ip subunits in the cytoplasm (41). A model for biosynthesis and membrane binding of SDH in B. subtilis is shown in Fig.…”
Section: Membrane Bindingmentioning
confidence: 99%
“…In no case did these correspond to the major arcs containing heme. This is interesting in view of the recent reports that in Bacillus subtilis, succinate dehydrogenase, solubilized in Triton X-100, is associated with a b-type cytochrome (14). In beef heart mitochondria, the succinate-ubiquinone oxidoreductase (complex II) is also associated with a unique b cytochrome (13).…”
Section: Discussionmentioning
confidence: 86%
“…One purpose of this paper is to demonstrate the utility of both isoelectric focusing (IEF) and crossed immunoelectrophoresis (CIE) for the resolution and analysis of the E. coli cytochromes. Both techniques have been previously applied successfully to the study of membrane proteins (14,26,27,36). In our study, four heme-containing protein complexes were resolved under nondenaturing conditions in the presence of Triton X-100.…”
mentioning
confidence: 99%
“…Succinate dehydrogenase [SDH; EC 1.3.99.1 succinate: (acceptor) oxidoreductase] is an enzyme which has been examined from a variety of eucaryotic and procaryotic sources (25). Most of the biochemical studies have been performed with the enzyme from beef heart mitochondria (11,16,28), but studies have also been reported on SDH from plant mitochondria (21,33), Neurospora crassa (45), Bacillus subtilis (22)(23)(24), Escherichia coli (8,34), Micrococcus luteus (9,10), Rhodospirillum rubrum (17,18), and Rhodopseudomonas sphaeroides (26). SDH from beef heart mitochondria and from Rhodospirillum rubrum can be removed from the membrane without the use of detergents by exposing the membranes either to alkaline conditions or to a chaotropic salt (25).…”
mentioning
confidence: 99%